Association of anxiety and depression symptoms with perceived health risk of nicotine vaping products for smoking cessation - Trigg, Joshua; Calabro, Ryan; Anastassiadis, Patrick; Bowden, Jacqueline; Bonevski, Billie (Frontiers in Psychiatry, 2024)
As tobacco smoking prevalence is unacceptably high for the one in five Australians reporting a mental health condition in the past year, multiple cessation supports are needed to reduce tobaccorelated disease. Nicotine vaping product (NVP)-facilitated smoking cessation is one option requiring a medical prescription in Australia. Yet, people easily obtain NVPs via non-prescription channels. As mental health impacts quitting intentions and health system engagement, this study examined how presence of anxiety and depression symptoms may be associated with perceived health risk of using NVPs from prescription or non-prescription sources for smoking cessation. We used cross-sectional South Australian (15 years +) 2022 survey data on vaping, smoking, anxiety, and depression. Robust linear regression was used to examine association of anxiety and depression symptoms and nicotine addiction concern on perceived health risk of using NVPs from prescription or non-prescription sources. For prescription NVPs, vaping was associated with lower perceived health risk (b=-0.732). Higher perceived addiction risk was associated with higher perceived health risk from prescription NVPs (b=0.784). For non-prescription NVPs, vaping (b=-0.661), or smoking (b=-0.310) was associated with lower perceived health risk, and higher perceived addiction risk (b=0.733) was associated with a higher perceived health risk. Although anxiety and depression were not directly associated with NVP health risk perceptions, vaping while having depression symptoms was associated with higher perceived health risk ratings for prescription (b=0.700) but not nonprescription sources. People with depression who vape may see health risk barriers in NVP prescription access for smoking cessation, a smoking cessation support gap.